(untitled) (Journal of Management and Educational Sciences, 2025)
The main purpose of these studies is to provide the information and understanding that organizations need to manage their human resources effectively and create a collaborative atmosphere. The research was conducted using the systematic review method. Human behavior in the workplace and how it affects organizational performance are the main topics of organizational behavior studies in Turkey. Leadership, motivation, job satisfaction, organizational commitment, organizational culture, communication and conflict resolution are among the main topics of organizational behavior studies in Turkey. Research on these topics helps companies understand their problems and create applicable answers. Research on organizational behavior is quite important in both academia and the commercial sector in Turkey. Business managers can improve organizational performance and human resource management by following these studies. This study examined how leadership, motivation, conflict resolution and job satisfaction (all subtopics of organizational behavior) are distributed in peer-reviewed journals by year from 2010 to 2024. According to the findings of the study, motivation has been the most important organizational behavior topic studied in Turkey from 2010 to 2024. Leadership and job satisfaction follow. According to the examined themes, the least studied topic was conflict management.